Diet Quality of Mothers of Children in NYC Head Start Is Not Associated With Child Adiposity. (7th June 2021) - Ashby-Thompson, Maxine; Goldstein, Inge; Contento, Isobel; Wolf, Randi; Jacobson, Judith
Abstract: Objectives: To assess whether maternal diet quality, measured when child was between ages 3 and 5, is associated with child overweight/obesity at ages 3 to 5. Methods: Baseline data from the Endotoxin Obesity and Asthma longitudinal study were used for these analyses. 380 African American and Hispanic mothers of children attending NYC Head Start answered a food frequency questionnaire (FFQ) about their own intake and a demographic questionnaire about themselves and child. FFQ data were converted to Healthy Eating Index (HEI)-2015 total scores (higher scores suggest better diet quality). Anthropometric measurements (weight, height, skinfolds, and waist circumference) were obtained from children. BMI, triceps and subscapular z-scores, and weight-to-height ratio (WHtR) were calculated. Results: Mean HEI total score at baseline was 64.3 ± 8.7 of 100 (considered a "D" grade or poor diet quality), but 69.8 ± 8.6 for Dominican and 60.2 ± 6.5 for Mexican mothers. Children were 50% female, 25% Mexican, 18% Dominican, 19% African American, 15% Puerto Rican and 23% Other. Mean age was 49 months. 52% of children fell below the 85 th percentile for BMI, 20% between 85 th and 95 th, and 28% above the 95 th percentile. Mother's HEI-2015 total score was not associated with child's BMI z-score (p = 0.830), child's triceps z-score (p = 0.77), child's subscapular z-score (p = 0.29), or child's WHtR (p = 0.83). More weight loss attempts by the mother (p = 0.03) and child's birthplace in (vs. outside) the United States (p = 0.01) were associated with higher BMI z-scores. Mexican ethnicity was associated with greater triceps z-scores (p = 0.03). Child's age was positively associated with subscapular z-score (p = 0.02). Child's age (p < 0.001) and Mexican ethnicity (p < 0.001) were associated with greater WHtR. Conclusions: Maternal diet quality was not associated with child adiposity; however, mother's weight loss attempts, child's age and being born in the US, and a child being identified as Mexican were related did. A novel maternal characteristic, number of weight loss attempts, and several child characteristics suggest targets for intervention. Funding Sources: National Heart, Lung, and Blood Institute; National Institute of Diabetes and Digestive and Kidney Diseases.